T cell-targeting nanoparticles focus delivery of immunotherapy to improve antitumor immunity - Daniela Schmid (Nature Portfolio, 2017)
Targeted delivery of immunomodulatory compounds to defined subsets of endogenous immune cells may improve the efficacy of combination immunotherapies. Here, the authors use PD-1-targeting nanoparticles containing a TGFβ inhibitor or a TLR7/8 agonist to deliver these payloads to T cells or via T cells to the tumor microenvironment, respectively, leading to anti-tumor efficacy in vivo.